Burnout Syndrome and its Risk Factors among Gynecology Consultants - Samar Hussain, Asma Yasin, Sumaira Mushtaq, Huma Tahseen, Saima Qurban, Mehvish Javeria (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Burnout as a condition characterised by emotional weariness, depersonalization (a propensity to show anti and cynical views about others) and a diminished feeling of personal success. In contrast to the more generalized concept of sadness, "burnout" describes a specific kind of fatigue that occurs in the job. Objective: The study’s objectives were to (a) determine whether or not burnout (emotional exhaustion, depersonalization, and personal professional achievement) is influenced by environmental factors (gender, age, marital status, years of professional experience, number of hours worked per week, teaching level, workplace), and (b) determine whether or not these factors are related. Study Design: Cross sectional study Study Setting: This study was conducted at Department of Obstetrics and Gynecology Rashid Latif Medical College Lahore from July 2022 to December 2022. Methodology: By using a systematic random sample, we were able to include 60 gynecologists. The proforma was given to them through email or print mail, and they were contacted individually. Doctors were told that by completing the anonymous proforma, after taking their consents. The study’s template has two sections. The participants’ demographic information was found in the first document. The second section was a copy of the Maslach Burnout Inventory (MBI). The 22-item MBI is scored on a 0–6-point Likert scale. SPSS version 20 was used to analyze the data. Results: In all, 60 gynecologists filled the performa. Participants mean ages ranged 40.55 ±6.0 years. Forty-seven of the participants were female (78.3%), whereas just four were male 13 (21.7%). The vast majority of guys had their FCPS, while married people made up the bulk of the sample 38(63.3%). In addition, 48 people (80%) were chosen field of expertise. In this study, participants were classified as burnt out if they had high EE in addition to high DP or low PPA. Over a quarter of consultants were suffering from burnout. At least 33 people The burnout prevalence rate among doctors whose annual salaries fall between 60 and 100,000 PKR is disproportionately high (Table 2). Low-income physicians had more burnout than high-income physicians (p= 0.014). Conclusion: Burnout syndrome is more common among female doctors than male. All aspects of burnout, but notably emotional weariness and depersonalization, are significantly impacted by insomnia and sadness, as are all aspects of alexithymia. Our research suggests that gynecologists may recover from burnout by focusing on their own well-being: as they age, gain experience, have families, and reduce the number of shifts they work each month. Keywords: burnout, burnout syndrome, gynecologist, Maslach Burnout Inventory, MIB